Synthesis of N-((2-hydroxynaphthalen-1-yl) (4-nitrophenyl) methyl)-N-methyl acetamide under solvent free condition, its characterization, antibacterial, antioxidant, computational and docking studies with HIV-1 protein - P. Vivekanandan, A. Daniel Aroquiaraj, K.S. Satheeshkumar, Francixavier Paularokiadoss, Bouzid Gassoumi and Sahbi Ayachi (South Eastern European Journal of Public Health, 2025)
In the present work, a competent and eco-friendly route for the synthesis of N-((2-hydroxynaphthalen-1-yl) (4-nitrophenyl) methyl)-N-methyl acetamide (HNMA) catalyzed by trichloroacetic acid and also using montmorillonite K10 clay under solvent free condition have been described. Thus, synthesized HNMA was characterized for its structure using spectroscopic tools such as UV-Visible, FT-IR, 1H NMR, 13C NMR and QTOF analyses. Under in vitro conditions, HNMA was found to exhibit potential antibacterial property against Escherichia coli and Staphylococcus aureus bacteria. In addition to the above, it exhibits excellent antioxidant property which was examined using DPPH radical scavenging capacity assay. Further, computational studies such as the electronic property along with its stability were studied by analyzed HOMO-LUMO gap. To understand charge distribution around HNMA molecule, Molecular Electrostatic Potential (MEP) study was performed which reveal that it has strong interaction with nucleophiles. Theoretical UV-Visible spectral analysis, infers that it has a quite higher optical band gap of 3.51 eV suggesting that HNMA primarily absorb ultraviolet light and appear transparent to visible light. Further structural and electronic properties of HNMA was investigated using infrared spectral study which conclude that it exhibit a strong intramolecular hydrogen bonding. Raman spectra of HNMA was simulated using density functional theory at the B3LYP/6-311G (d,p) level, which support its structure. The experimental 1H and 13C chemical shifts are in excellent agreement with the calculated values. The nonlinear optical (NLO) calculations indicate that it has higher dipole moment and hyperpolarizability. To further understand the nature of intra and intermolecular interactions between atoms and groups, quantum theory of atoms in molecules (QTAIM) analysis was also studied which indicate that the interactions are non-covalent in nature. Finally, docking study was performed to analyze its therapeutic activity against the target protein 1PVG, which is associated with HIV-1.